Duration and Judgments in Discussing the Past: Implications for the Spanish as a Second Language Classroom - Martínez-Arbelaiz, Asunción (2015)
En este estudio se analiza el uso del imperfecto en las narraciones de un grupo de estudiantes universitarios, antes y después de un curso de español en situación de inmersión. Aunque la cantidad de errores de imperfecto disminuye en las categorías observadas, se muestra que, a pesar de la instrucción recibida y de la exposición natural al input, persisten ciertos tipos de error en las narraciones, en particular los errores de uso de imperfecto relacionados con los conceptos de duración y valoración. In this study the use of the imperfect tense is analyzed in the compositions of a group of college students, before and after a Spanish course received in an immersion setting. Although the number of errors of the imperfect diminishes in the categories observed, it was shown that, despite the instruction received and the natural exposure to input, several types of errors are still present in the narratives. Errors in the use of imperfect related to the concepts of duration and judgment are particularly persistent.